Socioeconomic impact of agroforestry in Ludhiana (Punjab) - SINGH, SATWINDER; SINGH, AVTAR (The Indian Journal of Agricultural Sciences, 2018)
The study was performed with the objective to study socio-economic impact of agroforestry on farmers in Ludhiana (Punjab), India. Two types of respondents were selected, viz. agroforestry adopters and non-agroforestry adopters from the Ludhiana district (52 agroforestry adopters and 52 non-agroforestry adopters) were selected for the purpose of the study. The social and economic profile of the farmers was evaluated by asking them to fill a questionnaire and personal interviews. The impacts of socio-economic factors were assessed adopting standard methodology. Results pertaining to adoption of agroforestry revealed that majority of adopters were a graduate (48.08%) and most of them had mass media exposure (82.69%). Among agroforestry adopters, the operational land holdings were also large (36.53%). The other social factors like family type, extension contacts, residential area, livestock and presence of physical assets also reported differences among agroforestry adopters and non-adopters. The economic status of farmers revealed that poplar based system was more economical than pure cropping system during 2012-2017 (when the price was rs. 450/q or above) except 2016 when high fluctuation in the price of poplar was reported. Annuity value and benefit cost ratio (BCR) of agroforestry system were calculated to be higher than pure cropping system. During the year 2017, the BCR of agroforestry system was 4.32, whereas it was 3.31 for pure cropping system.